2018
DOI: 10.23893/1307-2080.aps.05609
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal omega-3 fatty acid supplementation on breast milk fatty acid composition

Abstract: Breast milk is the first source of omega-3 fatty acids (FA) for infants. We hypothesized that maternal omega-3 FAs supplementation affects the FA composition of breast milk. Thirtysix women received 950 mg omega-3 polyunsaturated (PUFA) supplementation per day for 9 months from 22-24 weeks of pregnancy until the 6 months of lactation and 26 women were enrolled as controls. Demographic data and nutritional status were taken by a questionnaire. Breast milk samples were collected at just after birth and 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Besides these findings, it is still not clear how the effects of ω-3 and ω-6 PUFA in the diets fed during gestation and lactation may be transmitted from the mother to the offspring. The dietary supplementation of ω-3 PUFA is known to induce changes in the milk fatty acid composition in several mammals, including pigs (YIN et al, 2017;NGUYEN et al, 2020), cows (MOALLEM, 2018;PALMQUIST, 2009), andhumans (MAZURIER et al, 2017;BÜYÜKUSLU et al, 2018). The use of ω-3 PUFA enriched diets has also been associated with an overall reduction in milk fat percentage of dairy cows (MOALLEM, 2018;MUSTAFA et al, 2003;DONOVAN et al, 2000), although no changes in milk protein (MOALLEM, 2018;MUSTAFA et al, 2003;AKRAIM et al, 2007) or milk lactose (DONOVAN et al, 2000;MOALLEM et al, 2013;GONTHIER et al, 2005) percentages have been found, and reports on the milk EV fraction were unavailable until now.…”
Section: Figure 1xosome Biogenesis With Main Molecules Shown To Affec...mentioning
confidence: 99%
“…Besides these findings, it is still not clear how the effects of ω-3 and ω-6 PUFA in the diets fed during gestation and lactation may be transmitted from the mother to the offspring. The dietary supplementation of ω-3 PUFA is known to induce changes in the milk fatty acid composition in several mammals, including pigs (YIN et al, 2017;NGUYEN et al, 2020), cows (MOALLEM, 2018;PALMQUIST, 2009), andhumans (MAZURIER et al, 2017;BÜYÜKUSLU et al, 2018). The use of ω-3 PUFA enriched diets has also been associated with an overall reduction in milk fat percentage of dairy cows (MOALLEM, 2018;MUSTAFA et al, 2003;DONOVAN et al, 2000), although no changes in milk protein (MOALLEM, 2018;MUSTAFA et al, 2003;AKRAIM et al, 2007) or milk lactose (DONOVAN et al, 2000;MOALLEM et al, 2013;GONTHIER et al, 2005) percentages have been found, and reports on the milk EV fraction were unavailable until now.…”
Section: Figure 1xosome Biogenesis With Main Molecules Shown To Affec...mentioning
confidence: 99%